PENGARUH KELAS BENIH DAN SISTEM TANAM TERHADAP HASIL PADI (Oryza sativa L.) - Hidayat, Wahyu; Kusdiarti, Lilik; Pamungkas, Djoko Heru (Universitas Sarjanawiyata Tamansiswa, 2017)
Study on the influence of seed and planting systems on rice (Oryza sativa L.) yield, aims to the determine the combination between seed classes with appropriate cropping systems in order to obtain maximum yield. The experiment was conducted in Jambidan village, Banguntapan subdistrict, Yogyakarta. The altitude is 100 m above sea level. The study has been done in October to December 2015. The rice variety used in this study was Ciherang. The treatment design used was a 3x3 factorial arranged in a randomized complete block design with three replicates. The first factor was the seed class of foundation seed, stock seed and certified seed. The second factor was the planting system consisting of three levels, namely tiles, legowo 1, and Legowo 4: 1. The variables observed were plant height, number of productive tiller, panicle length, number of grains per panicle, number of empty grains per panicle, and yield per hectare. Foundation seed produced maximum yield of 10.84 tons per hectare, then stock seeds of 10.47 tons per hectare, and certified seed yielding 9.76 tons per hectare. Planting system Legowo 2: 1 gave the highest yield of 11.06 tons per hectare, and planting system Legowo 4: 1 produced 10.59 tons per hectare, while tile system produced 9.40 tons per hectare.